INVESTIGATING THE EFFICACY AND SAFETY OF SGLT2 INHIBITORS FOR CARDIOVASCULAR PROTECTION IN PATIENTS WITH OBESITY AND TYPE 2 DIABETES (The Research of Medical Science Review, 2025)
Background: Obesity and type 2 diabetes mellitus (T2DM) are major risk factors for cardiovascular diseases (CVD), leading to significant morbidity and mortality. Objective: This study aimed to investigate the efficacy and safety of SGLT2 inhibitors for cardiovascular protection in patients with obesity and T2DM. Methods: This prospective observational study was conducted at Khawaja Safdar Medical College Sialkot during June 2022 to December 2023. A total of 235 participants were enrolled in the study. Results: The SGLT2 inhibitor group showed a significant reduction in the incidence of MACE (4.3%) compared to the placebo group (11.9%) (p = 0.02). Hospitalization for heart failure was also significantly lower in the SGLT2 inhibitor group (1.7%) compared to the placebo group (5.9%) (p = 0.03). Renal function was preserved in the SGLT2 inhibitor group, with an average increase in eGFR (+3.2 mL/min/1.73 m²) compared to a decrease in the placebo group (-5.8 mL/min/1.73 m²) (p = 0.01). HbA1c decreased more in the SGLT2 inhibitor group (-1.2%) compared to the placebo group (-0.3%) (p < 0.001). SGLT2 inhibitors also led to significant reductions in systolic and diastolic blood pressure and favorable changes in lipid profiles (p = 0.01). Conclusions: SGLT2 inhibitors significantly reduce cardiovascular events and improve renal function, glycemic control, blood pressure, and lipid profiles in patients with obesity and T2DM.